Comparison of Waist Circumference between Group of Office-based and Field Polices in The Department Police Pringsewu: Perbedaan Lingkar Perut sebagai Penentu Obesitas Sentral Antara Polisi Bagian Kantor dan Lapangan di Kepolisian Resor Pringsewu - Desti Ambar Wati (Universitas Widya Gama Mahakam Samarinda, 2024)
such as type 2 diabetes mellitus and cardiovascular disorders. The prevalence of central obesity in the population aged ≥15 years in Indonesia has shown an increase from 26.6% in 2013 to 31% in 2018. Central obesity occurs due to the accumulation of visceral fat, influenced by low levels of physical activity, particularly among office workers. The public health implications of this rise underscore the importance of interventions to reduce central obesity prevalence and promote an active and healthy lifestyle. This research aims to determine the waist circumference among police officers as a determinant of central obesity in the Pringsewu Police Resort. Method: This study is quantitative with a cross-sectional design. Sample selection uses accidental sampling technique, with a total of 77 participants. Waist circumference data were obtained through direct measurement using a medline. Data analysis was conducted using the Mann-Whitney test. Results: Police officers working in offices have a larger waist circumference (mean 96.57 cm) compared to those working in the field (mean 88.16 cm). Statistical analysis indicates a significant difference in waist circumference between office and field police officers (p = 0.012). Conclusion: The conclusion of this study is that police officers working in the office are at a higher risk of experiencing central obesity compared to those working in the field.